Functional roles and mechanisms of circRNA-protein interactions in cancer progression and tumor immune regulation - Yang, Lin; Li, Chunhong; Jiang, Xiulin; Yuan, Yixiao; Li, Chongxin; Zhou, Qiang; Wang, Qiang; Xiong, Jie (Frontiers in Immunology, 2026)
Circular RNAs (circRNAs) are a class of endogenous non-coding RNAs characterized by covalently closed loop structures, which confer high stability and evolutionary conservation. Beyond their well-known role as microRNA sponges, circRNAs can directly interact with proteins to modulate protein stability, activity, subcellular localization, and transcriptional or epigenetic regulation. These circRNA–protein interactions play critical roles in cancer progression by influencing tumor cell proliferation, metastasis, stemness, metabolic reprogramming, cell death, and therapy resistance. Moreover, they can shape the tumor immune microenvironment, affecting immune cell infiltration, immune evasion, and responses to immunotherapy. Understanding the mechanisms and functional consequences of circRNA–protein interactions provides new insights into tumor biology and offers promising avenues for cancer diagnosis, prognosis, and therapeutic intervention.